The interplay between magmatic and sedimentary processes on Noachian Mars and its implications for habitability - Tuhi, S.; Wray, J. J. (Frontiers in Astronomy and Space Sciences, 2026)
The Noachian epoch (∼4.1–3.7 Ga) on Mars was a formative period of its evolution marked by intense magmatic activity, pervasive surface weathering, and the extensive deposition of sedimentary deposits. Orbital and in situ observations have identified a complex interplay between volcanic and sedimentary processes that shaped Martian landscapes in the early era, which could have sustained habitable environments. Extensive magmatic activity, as represented by the formation of ancient highland volcanic provinces and large effusive eruptions, supplied the thermal energy, volatiles, and geochemical substrates for hydrothermal systems. Meanwhile, sedimentary activity, driven by fluvial, lacustrine, and aeolian activity, deposited phyllosilicate and sulfate-rich layered material, key indicators of aqueous alteration and environmental stability. The spatial and temporal coincidence between volcanic edifices and sedimentary basins, such as in igneous regions comprising Nili Fossae, Eridania Basin, and the boundary of Hellas, is suggestive of episodic linkage between magmatism and aqueous activity, with the possibility of long-lived hydrothermal environments. These environments would have provided stable redox gradients, nutrient fluxes, and liquid water on a long-term basis, which are all critical for life. Furthermore, the presence of alteration minerals like serpentine, smectites, and carbonates validates water-rock interaction hypotheses under neutral to alkaline conditions, which are favorable for microbial life. This review aims to synthesize current understanding of Noachian magmatic-sedimentary couplings and evaluate their geochemical and environmental implications for Martian habitability in the early epoch. While the duration and extent of these interactions remain uncertain, their geological and mineralogical signatures identify potential for habitable environments, offering valuable targets for future study of early Martian conditions.